1993
DOI: 10.1088/0953-8984/5/30/015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and neutron diffraction studies of dilute Cr-Re and Cr-Ru alloy single crystals

Abstract: Measurements are reponed on tbe temperature dependence of the elastic mnsmts of dilute Cr-Ru and Cr-Re alloy single crystals, wnta$ing respectively 0.3 at% Ru, 0.5 at.% Ru. 0.3 al. % Re and 0.5 at.% Re. Neutron diffraction experiments were also performed on lhe two Cr-Ru cryslals. Well defined anomalies were observed in all the elastic constants as well as in the integrated neutron intensities at the magnetic phase vansitions of the alloys.The commensurate (C) spin density wave (SDW) to paramagnetic (P) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…It is interesting to notice here that the values of β reported so far in the literature for chromium and its alloys agree with those found presently. For instance, Noakes et al estimated β = 0.3 for a single crystal Cr+0.2%V sample [10], Baran et al reported β ≈ 0.5 for single crystals of Cr + xAl (x = 1.2, 1.9 and 2.6 at%) [9], and Boshoff et al found β = 0.3-0.4 for a single crystal of Cr + yRu (y = 0.3, 0.5 at%) [11].…”
mentioning
confidence: 99%
“…It is interesting to notice here that the values of β reported so far in the literature for chromium and its alloys agree with those found presently. For instance, Noakes et al estimated β = 0.3 for a single crystal Cr+0.2%V sample [10], Baran et al reported β ≈ 0.5 for single crystals of Cr + xAl (x = 1.2, 1.9 and 2.6 at%) [9], and Boshoff et al found β = 0.3-0.4 for a single crystal of Cr + yRu (y = 0.3, 0.5 at%) [11].…”
mentioning
confidence: 99%
“…1 is not consistent with results on other Cr crystals having similar structures. First, a prominent sharp increase is expected 5,6 in the neutron intensity of Fig. 3͑b͒ on increasing the temperature through T IC , followed by a continuous decrease as the temperature increases towards T N .…”
Section: Resultsmentioning
confidence: 89%
“…The pattern in Fig. 2͑a͒ at Tϭ55 KϽT sf consists of two satellites, ͑Ϯ⑀,1,0͒, left and right of the central peak, ͑0,1,Ϯ⑀͒, and is characteristic 5 ISDW phase on heating. At T sf Ͻ235 KϽT 0 ͓Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These diagrams show a triple point concentration where the commensurate (C) spin-density-wave (SDW), the incommensurate (I) SDW and the paramagnetic (P) phases coexist. The Cr-Ru system is a typical example of this family of Cr alloys that has been studied extensively [1][2][3][4], particularly for alloy concentrations around the triple point concentration c t = 0.16 at.% Ru [1]. For c < c t a Cr-Ru alloy remains in the ISDW phase at all 0 < T < T N and the transition at the Néel temperature (T N ) is an ISDW-P phase transition.…”
Section: Introductionmentioning
confidence: 99%